2006
DOI: 10.1021/jm0600390
|View full text |Cite
|
Sign up to set email alerts
|

The Combi-Targeting Concept:  Synthesis of Stable Nitrosoureas Designed to Inhibit the Epidermal Growth Factor Receptor (EGFR)

Abstract: According to the "combi-targeting" concept, the EGFR tyrosine kinase (TK) inhibitory potency of compounds termed "combi-molecules" is critical for selective growth inhibition of tumor cells with disordered expression of EGFR or its closest family member erbB2. Here we report on the optimization of the EGFR TK inhibitory potency of the combi-molecules of the nitrosourea class by comparison with their aminoquinazoline and ureidoquinazoline precursors. This led to the discovery of a new structural parameter that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 26 publications
(42 reference statements)
2
47
0
Order By: Relevance
“…The growth of refractory tumors is driven by multiple signaling disorders that often cannot be blocked by the use of a single drug. The combi-molecule approach is the first that seeks to create molecules capable of blocking at least two divergent targets in the cells by allowing the intact molecules to block one target on their own and to degrade into other species directed at the same or different targets (18,20,22,23,26,40,41). To gain insight into the subcellular distribution and degradation of combimolecules, we designed a new prototype termed AL237 to (a) be fluorescent on its own and (b) degrade under physiologic conditions to FD105 (an EGFR inhibitor) that fluoresces in the blue and a DNA alkylating fragment that fluoresces in the green (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth of refractory tumors is driven by multiple signaling disorders that often cannot be blocked by the use of a single drug. The combi-molecule approach is the first that seeks to create molecules capable of blocking at least two divergent targets in the cells by allowing the intact molecules to block one target on their own and to degrade into other species directed at the same or different targets (18,20,22,23,26,40,41). To gain insight into the subcellular distribution and degradation of combimolecules, we designed a new prototype termed AL237 to (a) be fluorescent on its own and (b) degrade under physiologic conditions to FD105 (an EGFR inhibitor) that fluoresces in the blue and a DNA alkylating fragment that fluoresces in the green (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules, despite their combination-based design, were not developed with the purpose of eventually replacing the traditional chemotherapy but rather complementing it. Albeit, we showed that many prototypes (e.g., SMA41, FD137) showed stronger antiproliferative activity than classic combinations of drugs with the same mechanism of action (20,(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 91%
“…After filtration, the product obtained was washed with diethyl ether (3×10 mL) and was re-crystallized from methanol to give the pure corresponding compounds 10b. Yield 6-Nitroquinazolin-4-(3H)-one (11) 16) To 2 g of 2-amino-5-nitrobenzonitrile 1, 25 mL of formic acid were added and the mixture was refluxed for 6 h while stirring. The reaction mixture was then poured on ice water resulting in the formation of a yellow precipitate which was separated by filtration to give compound 11.…”
Section: General Synthesis Of Compounds 4a To 4lmentioning
confidence: 99%
“…Molecules designed to block EGFR TK, a class of potent, selective, ATP-competitive inhibitors of EGFR TK, induced signaling on their own and further degrade to a DNA damaging species, should induce significant cell-killing in tumours [9,10]. The first molecular probe designed to verify the combitargeting postulates, was shown to strongly block the EGFR TK activity on its own in a short exposure enzyme assay [11,12].…”
Section: Research Articlementioning
confidence: 99%